Dynamics of Pesantenan Keroncong in The Adaptation of Keroncong Music in Pati Post-Pandemic - Usready, Risma Febby Ayu; Rachman, Abdul (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2025)
This study investigates the persistence of the Pesantenan Keroncong group in Pati, employing cultural dynamics theory with a focus on intergenerational collaboration among musicians. The research object is the Pesantenan Keroncong group located in Dukuh Jl. Kunden Raya, Jambean, Sidokerto, Pati District, Pati City. The subjects of the study are the group leader and its members. Data were collected through observation, interviews, and documentation. Methodological triangulation ensured data validity, while data analysis involved data reduction, presentation, and interpretation. The findings reveal that the Pesantenan group maintains the presence of keroncong music through adaptation and innovation, such as rearranging modern songs and incorporating contemporary instruments. This demonstrates that cultural preservation can successfully coexist with societal progress. Guided by principles of preservation, utilization, and development, the Pesantenan Keroncong group not only safeguards cultural heritage but also actively promotes appreciation and love for keroncong music within the community.